2009
DOI: 10.1093/brain/awp046
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial changes within axons in multiple sclerosis

Abstract: Multiple sclerosis is the most common cause of non-traumatic neurological impairment in young adults. An energy deficient state has been implicated in the degeneration of axons, the pathological correlate of disease progression, in multiple sclerosis. Mitochondria are the most efficient producers of energy and play an important role in calcium homeostasis. We analysed the density and function of mitochondria using immunohistochemistry and histochemistry, respectively, in chronic active and inactive lesions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
346
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(386 citation statements)
references
References 55 publications
(94 reference statements)
25
346
1
8
Order By: Relevance
“…These spontaneous improvements may reflect either restored mitochondrial activity or a compensatory increase in the number of mitochondria. Histopathological studies found increased numbers of mitochondria and an upregulation of mitochondrial cytochrome C oxidase (complex IV) in axons in both chronic lesions and normal appearing white matter of MS subjects (Mahad et al, 2009;Witte et al, 2009). …”
Section: Axonal Energy Metabolismmentioning
confidence: 99%
“…These spontaneous improvements may reflect either restored mitochondrial activity or a compensatory increase in the number of mitochondria. Histopathological studies found increased numbers of mitochondria and an upregulation of mitochondrial cytochrome C oxidase (complex IV) in axons in both chronic lesions and normal appearing white matter of MS subjects (Mahad et al, 2009;Witte et al, 2009). …”
Section: Axonal Energy Metabolismmentioning
confidence: 99%
“…10 Dysfunctional mitochondria were recently shown to be implicated in both early and chronic stages of MS pathology, actively contributing to both axonal and neuronal injury. [11][12][13] The cause of mitochondrial dysfunction in patients with MS has been debated, but evidence is emerging that ROS production by macrophages/microglia might induce mitochondrial dysfunction in patients with MS, 10,13 possibly via oxidative damage to mitochondrial DNA. 12 Oxidative damage contribution to MS lesion formation In the initial phase of MS lesion formation, locally produced ROS can induce blood-brain barrier (BBB) disruption and promote leukocyte migration.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The cause of mitochondrial dysfunction in patients with MS has been debated, but evidence is emerging that ROS production by macrophages/microglia might induce mitochondrial dysfunction in patients with MS, 10,13 possibly via oxidative damage to mitochondrial DNA. 12 Oxidative damage contribution to MS lesion formation In the initial phase of MS lesion formation, locally produced ROS can induce blood-brain barrier (BBB) disruption and promote leukocyte migration. In vitro studies demonstrate that ROS promote BBB permeability, by causing cytoskeletal rearrangements in endothelial cells, and redistribution and loss of tight junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Although most demyelinated axons compensate for loss of oligodendrocytes/myelin, additional insults to axonal mitochondria impair axonal metabolism, increase axonal Ca 2+ , and promote progressive disruption of mitochondrial function (11,12). Changes in axonal mitochondria have been described in chronically demyelinated axons in postmortem multiple sclerosis tissue, and include decreased expression of nuclear-encoded mitochondrial genes (13), reduced mitochondrial respiration (14), and genetic alterations in mitochondrial DNA (15). A vicious cycle of reduced ATP production and increased axonal Ca 2+ results in degeneration of the chronically demyelinated axon.…”
mentioning
confidence: 99%